The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ultrasmedbio.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Staging Abdominal Aortic Aneurysm Disease With Pulse Wave Imaging

Abstract: The Abdominal Aortic Aneurysm (AAA) is a silent and often deadly vascular disease caused by the localized weakening of the arterial wall. Previous work has shown that local changes in wall stiffness can be detected with Pulse Wave Imaging (PWI), which is a noninvasive technique for tracking the propagation of pulse waves along the aorta at high spatial and temporal resolutions. This study aims at assessing the capability of PWI to monitor and stage AAA progression in a murine model of the disease. ApoE/TIMP-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…In agreement with previous work (19)(20)(21), the differences between aneurysm sacs and normal tissue are easily detected with PWI. From a qualitative perspective, the pulse waves propagate less uniformly in aneurysms and have lower displacement amplitudes, while from a quantitative perspective, PWV and the standard deviation of local PWV change significantly in aneurysms.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with previous work (19)(20)(21), the differences between aneurysm sacs and normal tissue are easily detected with PWI. From a qualitative perspective, the pulse waves propagate less uniformly in aneurysms and have lower displacement amplitudes, while from a quantitative perspective, PWV and the standard deviation of local PWV change significantly in aneurysms.…”
Section: Discussionsupporting
confidence: 92%
“…Previous work with the animal model used in this study has shown that changes in the overall diameter and stiffness of an aneurysm play an important role in staging the progression of aortic aneurysm disease (19). It is possible that in our study, we did not have sufficient statistical power to detect a difference in PWV or aneurysm diameter between the stable AAA and unstable AAA groups.…”
Section: Experimental Studies: Assessing the Stability Of Aortic Aneumentioning
confidence: 79%
See 3 more Smart Citations